Prostatic Inflammation's Effects on Individuals with Benign Prostate Hyperplasia's Clinical Consequences - Iqbal Shahzad, Muhammad Ali Yousuf, Khadim Hussain, Mumtaz Manzoor, Ghulam Mustafa Pathan, Tanveer Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: In order to ascertain the impact of silent inflammatory prostatitis on the clinical results of individuals receiving trans urethral prostate resection owing to benign prostatic hyperplasia. Study Design: Retrospective study Place and Duration: This retrospective study was conducted at Liaquat National Hospital Karachi in the period from April, 2022 to September, 2022. Methods: Total 330 patients were presented in this study. In this study, individuals over 45 years without a history of urologic surgery who presented to a urology clinic with lower urinary tract symptoms related to benign prostatic hyperplasia were included. Pathological outcomes and clinical indicators were evaluated before and one year after surgery. Mean Standard deviation was used to present data and categorical variables were assessed by frequencies and percentages. Results: Mean age of the patients was 61.3±10.42 years. Among 330 cases, 200 (60.6%) patients were had benign prostatic hyperplasia and 130 (39.4%) cases had both prostatic inflammation (category-IV) and benign prostatic hyperplasia. Before TURP, mean prostate volume in BP patients was 55.7±8.11 m3 and in BPH/PI patients was 55.3±10.6 m3 and after TURP mean prostate volume in BP patients was 23.2±1.20 m3 and in BPH/PI group 23.4±8.17 m3. We found that people with prostate inflammation had lower Qmax values and a higher preoperative prostate score compared to those who had no signs of inflammation before to prostate transurethral resection. Conclusion: In this study, we came to the conclusion that in individuals with benign prostatic hyperplasia, prostate inflammation without symptoms might worsen lower urinary tract symptoms and the rate of urine flow. Keywords: Benign Prostatic Hyperplasia (BPH), Prostate Pathology, Prostatic Inflammation